The impact of skin involvement on the psychological well-being of patients with Sarcoidosis: Skin involvement in sarcoidosis - AlRyalat, Saif Aldeen; Malkawi, Lna; Abu-Hassan, Hana; Al-Ryalat, Nosaiba (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: Physicians frequently face challenges when screening and managing mental health impairment caused by different diseases, particularly those involving the skin. Objective: We aim to identify the major aspects of mental health impairment related to secondary skin involvement occurring in sarcoidosis patients. Methods: A total of 718 patients with a biopsy-confirmed diagnosis of sarcoidosis were included from the A Case Control Etiologic Study of Sarcoidosis (ACCESS) study. Sample was divided into two groups depending on presence or absence of skin involvement. Each recruited patient underwent mental health assessment using two measures: depression and mood scales. Demographic data of participants was obtained. Results: A total of 143 sarcoidosis patients had secondary skin involvement, and 575 had no skin involvement. Sarcoidosis patients with skin involvement had lost their appetite more frequently, experienced low mood more frequently, and had frequently encountered a significant loss of acceptance compared to patients without skin involvement. Conclusion: A multidisciplinary approach including a focused psychological assessment for patients with sarcoidosis; particularly those with skin involvement, is encouraged.